Automated Laser‐Transfer Synthesis of High‐Density Microarrays for Infectious Disease Screening. Issue 23 (28th April 2022) - Paris, Grigori; Heidepriem, Jasmin; Tsouka, Alexandra; Liu, Yuxin; Mattes, Daniela S.; Pinzón Martín, Sandra; Dallabernardina, Pietro; Mende, Marco; Lindner, Celina; Wawrzinek, Robert; Rademacher, Christoph; Seeberger, Peter H.; et al.
Abstract: Laser‐induced forward transfer (LIFT) is a rapid laser‐patterning technique for high‐throughput combinatorial synthesis directly on glass slides. A lack of automation and precision limits LIFT applications to simple proof‐of‐concept syntheses of fewer than 100 compounds. Here, an automated synthesis instrument is reported that combines laser transfer and robotics for parallel synthesis in a microarray format with up to 10 000 individual reactions cm − 2 . An optimized pipeline for amide bond formation is the basis for preparing complex peptide microarrays with thousands of different sequences in high yield with high reproducibility. The resulting peptide arrays are of higher quality than commercial peptide arrays. More than 4800 15‐residue peptides resembling the entire Ebola virus proteome on a microarray are synthesized to study the antibody response of an Ebola virus infection survivor. Known and unknown epitopes that serve now as a basis for Ebola diagnostic development are identified. The versatility and precision of the synthesizer is demonstrated by in situ synthesis of fluorescent molecules via Schiff base reaction and multi‐step patterning of precisely definable amounts of fluorophores. This automated laser transfer synthesis approach opens new avenues for high‐throughput chemical synthesis and biological screening. Abstract : An automated laser‐based synthesis machine is presented, combining laser‐induced forward transfer and robotics to perform parallel chemistry in the microarray format with up to 10 000 individual reactions cm − 2 . By developing an optimization pipeline, peptide microarrays with thousands of different sequences can be synthesized in high yield to study the antibody responses in infectious disease patients.